Oxidative stress in cerebrovascular disease and associated diseases - Kumar, Vijay; Bishayee, Kausik; Park, Soochul; Lee, Unjoo; Kim, Jaebong (Frontiers in Endocrinology, 2023)
Cellular aging is the most severe risk factor for neurodegenerative disease. Oxidative stress (OS) is a critical factor in the aging process, resulting from an imbalance between reactive oxygen species (ROS) and the antioxidant defense system. Emerging evidence indicates that OS is a common cause of several age-related brain pathologies, including cerebrovascular diseases. In this review, we summarize evidence supporting an active role of OS in cerebrovascular disease progression, focusing primarily on stroke pathogenesis. Furthermore, we discuss associated factors that influence stroke accidents as well as the current pharmaceutics/therapeutics available for treating several cerebrovascular diseases.